The study of the dependence of magnetic field gradient on parameters of the part being tested by the pulsed magnetic non-destructive testing method - O. V. Tarasenko; Yu. V. Kreselyuk; M. N. Ivlev (Омский научный вестник)
An assessment is made of the influence of the parameters of a controlled part by the magnetic method of non-destructive testing on the gradient of the magnetic field strength of the measuring transducer. A simplified design of a pulsed gradiometric transducer is presented, and its parameters for conducting experiments are indicated. A mathematical model for calculating the output signal of a gradiometer fluxgate used to obtain output data is considered. The dependences of the magnetic field intensity gradient on the distance between the sensor and the plane of the controlled part, on the coercive force and thickness of the hardened layer, as well as on the thickness of the controlled part are studied. Conclusions are drawn based of the experiment performed.